2004
DOI: 10.3748/wjg.v10.i24.3583
|View full text |Cite
|
Sign up to set email alerts
|

The effect of adenovirus expressing wild-type p53 on 5-fluorouracil chemosensitivity is related to p53 status in pancreatic cancer cell lines

Abstract: Our results suggest that Ad-p53 may synergistically enhance 5-FU-chemosensitivity most strikingly in pancreatic cancer cells lacking p53 function. These findings illustrate that the anticancer efficacy of this combination treatment is dependent on the p53 gene status of the target tumor cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…Sequencing analysis was also performed on exons 1 and 2 of the K-ras gene and exons 5, 6, 7 and 8 of p53 to verify data reported in the literature. 24,25 Flow cytometric analysis-cell cycle perturbation analysis. Exponentially growing cells were trypsinized and 2 x 10 5 cells/60-mm Petri dish were incubated for 18-24 h at 37˚C before drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Sequencing analysis was also performed on exons 1 and 2 of the K-ras gene and exons 5, 6, 7 and 8 of p53 to verify data reported in the literature. 24,25 Flow cytometric analysis-cell cycle perturbation analysis. Exponentially growing cells were trypsinized and 2 x 10 5 cells/60-mm Petri dish were incubated for 18-24 h at 37˚C before drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Chemotherapy with 5-FU was largely ineffective in hPANC-1 cells probably because of inactivation in this cell line of the p53 gene, which is implicated in cell cycle arrest (Eisold et al 2004). The p53 tumor suppressor gene is functionally inactivated in about 50% of all human malignancies, including up to 60% of pancreatic cancer .…”
Section: Tablementioning
confidence: 99%
“…The p53 tumor suppressor gene is functionally inactivated in about 50% of all human malignancies, including up to 60% of pancreatic cancer . Indeed several reports have suggested that the p53 status of the tumor cells may be an important response determinant to 5-FU-based chemotherapy (Ahnen et al 1998, Lenz et al 1998, Eisold et al 2004. Even though we already knew that expression of wt-p53 was required for 5-FU-induced apoptosis and to potentiate the 5-FU-cytotoxicity (Lowe et al 1993, Bunz et al 1999, Eisold et al 2004, we decided to verify if the combination 5-FU and T 3 could inhibit the tumor proliferation in a p53-independent manner (Dinda et al 2002).…”
Section: Tablementioning
confidence: 99%
See 2 more Smart Citations